Seleção entre e dentro de população base de pimenteiras para fins ornamentais - Ferreira, Karmita Thainá Correia (2016)
Peppers belong to Capsicum and has great economic importance in the world, as a spice and as an ornamental because of the wide variety of shapes and colors. The existence of variety makes possible the use of pepper in breeding programs, thus meet the commercial demand. The selection of plants in segregating generations and evaluation in the populations is of fundamental importance in ensuring that the best hybrid combinations will advance generations and finally form the new variety. The objective this work were used to evaluate divergence among seven phenotypic classes of Capsicum annuum, in a F3 segregating generation belonging to the germplasm bank of Universidade Federal da Paraíba-UFPB. Seven families were used (UFPB 17, UFPB 30, UFPB 35, UFPB 47, UFPB 53, UFPB 55 e UFPB 56) (Capsicum annuum L.). Quantitative (24) and qualitative (26) descriptors proposed by the International Plant Genetic Resources Institute were used. The experiment was conducted in a greenhouse. Grouping of genotypes used Tocher’s method based on Mahalanobis distance. According to Tocher method 8 groups were formed, the characteristics that most contributed to the diversity were number of fruits per plant, dry matter content and number of seeds per fruit. The stigma length features, length of anther and number of stamens did not contribute to the genetic divergence can ruled out in future studies.